2021
DOI: 10.2196/14004
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Digital Smartphone Mental Health Apps Among Adolescents: Qualitative Interview Study

Abstract: Background Mental health digital apps hold promise for providing scalable solutions to individual self-care, education, and illness prevention. However, a problem with these apps is that they lack engaging user interfaces and experiences and thus potentially result in high attrition. Although guidelines for new digital interventions for adults have begun to examine engagement, there is a paucity of evidence on how to best address digital interventions for adolescents. As adolescence is a period of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…Similarly, diverse preferences were found with gamification elements of Match Emoji. The various preferences toward micromessages and game features among participants are consistent with the literature that suggests adolescents have different opinions about the type of DMHI they are attracted to [ 42 , 43 ]. Thus, while some adolescents may be frequent CVG users and interested in gamification elements, others may be less focused on these features and more attracted to learning about mental health and well-being [ 44 ].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, diverse preferences were found with gamification elements of Match Emoji. The various preferences toward micromessages and game features among participants are consistent with the literature that suggests adolescents have different opinions about the type of DMHI they are attracted to [ 42 , 43 ]. Thus, while some adolescents may be frequent CVG users and interested in gamification elements, others may be less focused on these features and more attracted to learning about mental health and well-being [ 44 ].…”
Section: Discussionsupporting
confidence: 83%
“…Current access to CAMHS is universally poor ( 64 ) and there is growing evidence post-COVID-19 of the need for sustained implementation of digital tools and interventions to encourage both help-seeking and competence by CYP ( 65 , 66 ). There is also evidence that DHIs could cater to diverse mental health problems at scale for CYP ( 67 , 68 ). Within the current study, our results suggested that DHIs that responded to OCSA were of particular interest to practitioners given the perceived lack of resources available to them and were seen as potentially stand-alone interventions or ones which would complement existing therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-structured interview. The semi-structured interview has been adapted from a previous qualitative study, assessing preferences for digital smartphone mental health apps amongst adolescents (Ribanszki et al, 2021). The interview questions (Extended data) are designed to assess end user's experience of the app, the relatability of app content, and to gain feedback on any aspects of the app end users would change.…”
Section: App Usage Informationmentioning
confidence: 99%